Roman letters : an anthology - Zeiner-Carmichael, Noelle, 1974- (Chichester, West Sussex : Wiley-Blackwell, 2014)
Roman Letters offers a rich selection of original translations of ancient Roman letters spanning from the 1st century BCE to the 2nd century CE. Chronologically arranged and grouped according to author or collection, the letters cover various topics and themes selected from a broad range of authors. A unique single volume text that makes classical letters accessible and readable to undergraduates and the non-specialist reader Presents a wide range of authors and material, with over 200 selected texts Includes selections that illustrate a complete cycle of correspondence, as well as letters written by the same author and covering the same topic/theme but sent to different recipients Letters are arranged chronologically, with letters grouped according to author or collection An accompanying website offers additional, complementary letters Topical index highlights various topics and themes represented by the letters.
1. Letters and Letter-Writing in Ancient Rome -- 2. The Roman Republic (70 BCE-27 BCE) -- 3. The Augustan Age (27 BCE-14 CE) -- 4. The Roman Empire (14 CE-3rd century CE) -- 5. Epistolary Theorists
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 1. století př. Kr.-2. století po Kr; korespondence -- starověký Řím -- 1. století př. Kr.-2. století po Kr; latinští starověcí autoři -- starověký Řím -- 1. století př. Kr.-2. století po Kr; panovníci -- starověký Řím -- 1. století př. Kr.-2. století po Kr; correspondence -- ancient Rome -- 1st century B.C.-2nd century A.D.; ancient Latin authors -- ancient Rome -- 1st century B.C.-2nd century A.D.; kings and rulers -- ancient Rome -- 1st century B.C.-2nd century A.D.; korespondence; antologie; e-knihy online; correspondence; anthology; e-books online